1980
DOI: 10.1038/bjc.1980.284
|View full text |Cite
|
Sign up to set email alerts
|

Surface proteins in normal and transformed rat liver epithelial cells in culture

Abstract: Summary.-The pattern of surface proteins of different types of normal and transformed rat liver cells have been studied in culture by means of lactoperoxidasecatalysed iodination procedures, followed by SDS-gel electrophoresis. The cells examined were primary cultures of epithelial liver cells, long-term cultures of epithelial liver cells, in vitro transformed epithelial liver cell lines and liver tumourcell lines; mesenchymal cells from liver and skin were also examined. The principal surface proteins of prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Our results are in agreement with Defendi et al (1982), who found increased cellsurface fibronectin in SV4O-transformed keratinocytes, and in general agreement with other reports on the effects of transformation in other epithelial cell systems. For instance, although it has been reported that some transformed rat liver epithelial cells have no cell-surface fibronectin (Karasaki et al, 1980;Rieber and Rieber, 1980), others have shown in larger studies that the majority of transformed rat liver epithelial cells retain fibronectin (Bannikov et al, 1980;Paraskeva and Gallimore, 1980;Goldstein and Fisher, 1981). Similarly, virally transformed mouse epithelial cells (Keski-Oja et al, 1982) and chemically transformed mouse salivary gland and bladder epithelial cells (Wigley and Summerhayes, 1979) all retain extracellular fibronectin.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with Defendi et al (1982), who found increased cellsurface fibronectin in SV4O-transformed keratinocytes, and in general agreement with other reports on the effects of transformation in other epithelial cell systems. For instance, although it has been reported that some transformed rat liver epithelial cells have no cell-surface fibronectin (Karasaki et al, 1980;Rieber and Rieber, 1980), others have shown in larger studies that the majority of transformed rat liver epithelial cells retain fibronectin (Bannikov et al, 1980;Paraskeva and Gallimore, 1980;Goldstein and Fisher, 1981). Similarly, virally transformed mouse epithelial cells (Keski-Oja et al, 1982) and chemically transformed mouse salivary gland and bladder epithelial cells (Wigley and Summerhayes, 1979) all retain extracellular fibronectin.…”
Section: Discussionmentioning
confidence: 99%
“…The surface proteins of normal and transformed mesenchymal and epithelial rat liver cells have been examined by means of lactoperoxidase-catalyzed iodination procedures, followed by sodium dodecyl sulphate gel electrophoresis. 29 The pattern of iodinazable surface proteins of primary cultures of liver epithelial cells was quite different from, and more complex than, that observed in liver mesenchymal cells. The epithelial liver cells were shown to possess a surface protein of the same molecular weight of the "fibroblastic" fibronechm In addition, other surface proteins of lower molecular weight, which appear to be specific to this type of epithelial cell, were present.…”
Section: Surface Proteins In Rat Liver Epithelial Cellsmentioning
confidence: 87%